Grayeagle - Arkoff, Samuel Z., 1918-2001.; Pierce, Charles B.; Mendoza-Nava, Jaime, 1925-2005.; Johnson, Ben, 1918-1996.; Cord, Alex.; Cody, Iron Eyes, 1904-1999.; Wood, Lana, 1946-; Elam, Jack, 1920-2003.; Fix, Paul, 1901-1983.; Clem, Jimmy; Daniels, Jacob; Butler, Cindy; et al. (Los Angeles Twentieth Century Fox Home Entertainment, 2011)
In Montana in 1848, Grayeagle, a handsome young Cheyenne warrior, kidnaps Beth, daughter of a wealthy trapper, setting in motion a fierce manhunt. During the pursuit, Beth discovers that she is really the daughter of the dying Cheyenne chief, and in the end she must make a choice from which there can be no turning back.
Originally released as a motion picture in 1977.
Title from container.
Music, Jaime Mendoza-Nava.
Ben Johnson, Iron Eyes Cody, Alex Cord, Lana Wood, Jack Elam, Paul Fix, Jimmy Clem, Jacob Daniels, Cindy Butler, Charles B. Pierce.
MPAA rating: PG.
DVD-R format (This disc is expected to play back in DVD video "play only" devices, and may not play in other DVD devices, including recorders and PC drives.); 16x9 2.35 letterbox; Dolby digital; NTSC region 1.
Keywords: Cheyenne Indians -- Drama; Kidnapping -- Drama; Indians of North America -- Montana -- Drama; Montana -- Drama; Drama; Feature films; Fiction films; Western films